Small wind energy harvesting using piezoelectric materials - Ng, Jonathan Tian Loong (2014)
Hospitals, bridges and tunnels are important man-made infrastructures that support the human way of life. These structures are vital and are prone to natural disasters and aging. Structural health monitoring involves the use of wireless sensors networks (WSN) that monitors the structural integrity of the building. The sensor networks are powered by batteries, in which the power supply is finite and would require replacement. When there is no power, the sensors would not function and damages in the buildings would go unnoticed. Hence, there is a need for a sustainable energy source; this is to ensure that the buildings are monitored constantly. Wind, solar and vibration energy are known renewable energy source. These are found in the ambient environment and are largely untapped. Piezoelectric materials allow strain energy to be harvested. Strain energy can be converted from wind or vibration energy. As there is much interest in the field of energy harvesting, innovative designs and configurations of harvesters are appearing each day. Large-scale wind energy is harvested by wind mill farms found on offshore islands and places with high altitudes. Wind is random and can be found anywhere. For harvesting to be effective, a constant wind source is needed. Small-scale wind energy can be found in air conditioning and ventilation ducts. This consists of low wind velocities that could be harvested. The study will propose a few harvester prototypes designs and experiments would be conducted to see if the designs are viable. If viable, these would improve the wireless sensor networks as independent and sustainable systems.